Land's End: Capitalist Relations on an Indigenous Frontier - White, Ben (Kasarinlan: Philippine Journal of Third World Studies; Vol 30, No 2-Vol 31, No 1 (2015-2016): Indigenous People and Contested Access to Land, 2017)
Book review of Li, Tania Murray. 2014. Land’s End: Capitalist Relations on an Indigenous Frontier. Durham, North Carolina and London: Duke University Press. 225 + xiv pp.